Comparison of the safety and pharmacokinetics of ST-246® after i.v. infusion or oral administration in mice, rabbits and monkeys. - Yali Chen (Public Library of Science (PLoS), 2011)
Background ST-246® is an antiviral, orally bioavailable small molecule in clinical development for treatment of orthopoxvirus infections. An intravenous (i.v.) formulation may be required for some hospitalized patients who are unable to take oral medication. An i.v. formulation has been evaluated in three species previously used in evaluation of both efficacy and toxicology of the oral formulation. Methodology/principal findings The pharmacokinetics of ST-246 after i.v. infusions in mice, rabbits and nonhuman primates (NHP) were compared to those obtained after oral administration. Ten minute i.v. infusions of ST-246 at doses of 3, 10, 30, and 75 mg/kg in mice produced peak plasma concentrations ranging from 16.9 to 238 µg/mL. Elimination appeared predominately first-order and exposure dose-proportional up to 30 mg/kg. Short i.v. infusions (5 to 15 minutes) in rabbits resulted in rapid distribution followed by slower elimination. Intravenous infusions in NHP were conducted at doses of 1 to 30 mg/kg. The length of single infusions in NHP ranged from 4 to 6 hours. The pharmacokinetics and tolerability for the two highest doses were evaluated when administered as two equivalent 4 hour infusions initiated 12 hours apart. Terminal elimination half-lives in all species for oral and i.v. infusions were similar. Dose-limiting central nervous system effects were identified in all three species and appeared related to high C(max) plasma concentrations. These effects were eliminated using slower i.v. infusions. Conclusions/significance Pharmacokinetic profiles after i.v. infusion compared to those observed after oral administration demonstrated the necessity of longer i.v. infusions to (1) mimic the plasma exposure observed after oral administration and (2) avoid C(max) associated toxicity. Shorter infusions at higher doses in NHP resulted in decreased clearance, suggesting saturated distribution or elimination. Elimination half-lives in all species were similar between oral and i.v. administration. The administration of ST-246 was well tolerated as a slow i.v. infusion.